Evaluate the Anti-inflammatory Effects of Nanocinnamon Gel on Salivary Cytokines: Tumor Necrosis factor-alpha (TNF-α) and Interleukine-6 (IL-6) in Chronic Gingivitis - Zahraa MS.Ali; Jawnaa K. Mammdoh; Amer A Taqa (University of Mosul, College of Dentistry, 2021)
Aims: The study aimed to evaluate the anti-inflammatory effects of nanocinnamon gel on salivary concentrations of cytokines: interleukine-6( IL-6) and tumor necrosis factor-alpha ( TNF-α) in chronic gingivitis.Material and Methods: prepared nanocinnamon gel 2% concentration from nanocinnamon powder. The study was carried out on the randomized clinical trial of chronic gingivitis comprises of 45 patients of age between (18-50)years old .They were divided into three groups, fifteen for each group , treatment involved mechanical therapy by scaling and polishing at dental clinic and drug treatment in which the first group applied to the mechanical treatment alone, , second group received chlorhexidine gel topically and third group received nanocinnamon gel topically , the treated groups used the gel twice daily at least ten minute for three weeks. Unstimulated saliva was collected for each individuals and at least two hours after any food intake to disregard the food stimulatory effect on salivary secretions. ELISA kits (Enzyme Linked Immunosorbent Assay) used to measure IL-6 and TNF-α in saliva . Data were analyzed using kruscal-wallias H test and Friedmans̓ test analysis range test. Results: the results of present study showed that there were no significant differences in salivary IL-6 among groups after treatment however , there were significantly decreasing in salivary TNF-α of nanocinnamon group after 21 days of interval therapy in comparison to control group. Conclusion :The use of nanocinnamon gel have anti-inflammatory effect against gingivitis and the changes in the salivary concentrations of IL-6 and TNF-α can help in the diagnosis of periodontal disease